The Role of Training and Work-Related Injury on Home Health Workers' Job Satisfaction: Analysis of the National Home and Hospice Care Survey. Issue 4 (November 2019) - Hamadi, Hanadi; Probst, Janice C.; Khan, M. Mahmud; Tafili, Aurora
The purpose of this study was to describe personal, job, agency, environmental, and ergonomic factors that affect job satisfaction among home health workers (HHWs). A cross-sectional design was conducted, and data from the National Home and Hospice Care Survey ( N = 3, 274) were analyzed using a multilevel structural equation model (generalized structural equation model). HHWs with excellent training knowledge were about 1.5 times more likely to report a higher degree of job satisfaction compared with those with poor training knowledge, and those who reported a work-related injury were 66% more likely to report lower job satisfaction score. Job satisfaction is associated with work environment, leadership support, and work-related training. Future research and a follow-up survey are needed to understand HHWs' workforce and be better positioned to meet their need so that they may meet the need of the aging population.